Management of iron deficiency anemia during pregnancy: a midwife-led continuity of care model - Naz, Sabahat; Shahid, Shahira; Noorani, Sahir; Fatima, Ishrat; Jaffar, Ali; Kashif, Muhammad; Yazdani, Nida; Khan, Uzma; Rizvi, Arjumand; Nisar, Muhammad Imran; Jehan, Fyezah; Hoodbhoy, Zahra (Frontiers in Nutrition, 2024)
Background: Globally, 36.5% of pregnancies are affected by anemia, particularly in low-and middle-income countries, posing significant risks to maternal and perinatal health. In rural Pakistan, 44.3% of pregnant women suffer from iron deficiency, contributing to the high prevalence of anemia. Limited accessibility to antenatal care exacerbates the challenge, necessitating innovative solutions. This study assessed a midwife-led continuity of care model, utilizing intravenous (IV) iron therapy for the management of anemia in Karachi, Pakistan. Methods: We performed a retrospective analysis of data from a prospective cohort study conducted in two primary healthcare facilities, which employed a community midwife (CMW)-led continuity of care model for antenatal care, including IV iron therapy. We extracted data from February 2021 to March 2022 for women who were diagnosed with anemia based on hemoglobin (Hb) levels, categorized as mild (10.0 to 10.9 g/dL), moderate (7.0 to 9.9 g/dL), or severe (less than 7.0 g/dL). Assessment occurred at the initial antenatal care (ANC) visit to establish baseline anemia severity, and approximately two weeks after intravenous (IV) iron therapy administration to evaluate post-treatment changes were considered. Results: We enrolled 114 pregnant women, where the majority presented with moderate (88.6%) anemia. After IV iron treatment, 48.5% improved to normal-mild levels, while 50% remained unchanged. Severe anemia affected 10.5% at baseline; 42% shifted to moderate and 50% to normal-mild post-treatment, with one remaining unchanged (p<0.001). Among women enrolled in the first and second trimesters, severe anemia improved to normal-mild (50%) and moderate levels (50%) (pre-treatment: n=10, post-treatment: n=0), and moderate anemia decreased by 48% (pre-treatment: n=92, post-treatment: n=47). Conclusion: Our midwife-led model of care demonstrated an improvement in iron levels among pregnant women. The model addressed the challenges of anemia prevalence in Pakistan and underscored the significance of empowering front-line healthcare providers, such as community midwives (CMWs) for managing these common conditions.